Can green location-oriented policies promote substantive green innovation by enterprises? Evidence from China's National Eco-Industrial Demonstration Parks. - Juying Tian; Wei Qiu (PLoS ONE, 2025)
Corporate green innovation is a key practice driving sustainable economic development. Exploring the effectiveness of green location-oriented policies in fostering substantial green innovation among micro-enterprises through a "point-to-area" approach holds practical importance. Drawing on the practice of China's National Eco-Industrial Demonstration Parks (NEDPs) and utilizing data from A-share listed companies in Shanghai and Shenzhen spanning the period from 2007 to 2022, this paper utilizes a staggered Difference-in-Differences methodology to examine the impact and mechanism of green location-oriented policies on corporate substantial green innovation. The study reveals that the establishment of NEDPs can stimulate substantial green innovation among corporations, with this finding retaining its validity after undergoing a series of robustness test. Analysis of heterogeneity indicates that the incentive effect of NEDPs on corporate substantial green innovation is mainly concentrated in enterprises with low strategic differentiation, low carbon emission performance, and those located in resource-based urban areas. Mechanism analysis indicates that NEDPs jointly promote substantial corporate green innovation mainly through the pressure effects of increased government environmental attention and corporate investment in research and experimental development as well as the incentive effects of green financial support and innovative talent agglomeration. This paper enriches the research on the antecedents of corporate green innovation behavior and provides new micro-level evidence for the effectiveness of green location-oriented policies. It is recommended that governments should con-tenuously strengthen green attention, increase green investment guidance, and cluster innovation factors to effectively promote corporate substantial green innovation.